1990
DOI: 10.1111/j.1365-2044.1990.tb14779.x
|View full text |Cite
|
Sign up to set email alerts
|

Meningitis after obstetric spinal anaesthesia

Abstract: SummaryA case of meningitis after obstetric spinal anaesthesia is reported. The possible aetiological causes of postspinal meningitis are discussed and the dificulty in diferentiation between aseptic and bacterial meningitis noted. Ways to reduce the risk of bacterial contamination of cerebrospinaljuid are mentioned. The patient in this case made a full recovery, but the use of spinal anaesthesia in these patients is open to question.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

1992
1992
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(12 citation statements)
references
References 9 publications
0
11
0
1
Order By: Relevance
“…Dural puncture during bacteraemia may facilitate the entrance of bacteria into the CSF, but septic patients should only be submitted to regional anesthesia after a clinical response to antibiotics has been established (29). Endogenous sources of bacteria such as poor dental health (30), urinary tract infection (31), or manipulation of retained placenta (32) have been associated with meningitis. In the present study no patient had a preoperative diagnosis of an infectious disease.…”
Section: Literature Review and Discussionmentioning
confidence: 99%
“…Dural puncture during bacteraemia may facilitate the entrance of bacteria into the CSF, but septic patients should only be submitted to regional anesthesia after a clinical response to antibiotics has been established (29). Endogenous sources of bacteria such as poor dental health (30), urinary tract infection (31), or manipulation of retained placenta (32) have been associated with meningitis. In the present study no patient had a preoperative diagnosis of an infectious disease.…”
Section: Literature Review and Discussionmentioning
confidence: 99%
“…Other infective complications of extradural anaesthesia in obstetrics have included non-abscess infection of the extradural space [24] and meningitis [25]. Meningitis has also been described after spinal anaesthesia in obstetrics [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, judging by the numbers of published cases, it could be the second commonest neurological complication of neuraxial analgesia in labour, after paraesthesiae. Loo et al 6 found 20 cases, 31,[43][44][45][46][47][48][49][50][51][52][53][54] while at least seven others [55][56][57][58][59][60][61] and one case of Herpes simplex encephalitis 62 among parturients, and dozens more among non-obstetric patients, have been reported since.…”
Section: Sources Of Infectionmentioning
confidence: 98%